Kebijakan Strategis: Transformasi Kantor Wilayah Kementerian Agama Sumatera Utara Menuju Tata Kelola Berkesadaran Ekoteologi - Azizah Hanim Nasution (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy study aims to analyze the failure of the Ecotheology program implementation in bureaucratic governance (good governance) within the Regional Office of the Ministry of Religious Affairs (Kanwil Kemenag) of North Sumatra Province and recommend appropriate regulatory solutions. The main issue identified is the failure of Kanwil Kemenag to realize environmentally conscious governance due to the low internalization of Ecotheology values ​​​​among the State Civil Apparatus (ASN), exacerbated by weak leadership role models and inconsistent Green Office culture. The writing method used is Qualitative Policy Analysis with a descriptive-prescriptive approach. The descriptive approach is used to identify the root of the problem through Root Cause Analysis and Evidence Synthesis techniques (regulation analysis and internal reports), while the prescriptive approach is used to formulate recommendations. For evaluation of policy alternatives, William N. Dunn's Alternative Policy Criteria Scoring theory is used (Effectiveness, Efficiency, Equity, Acceptability) to ensure the feasibility of solutions. The results of the analysis indicate that the root of the problem lies in cultural pathology and leadership crisis, not in the absence of a program, as evidenced by the highest score on the issue of internalization of values. Based on the Dunn criteria evaluation, the best policy alternative is regulatory intervention at the value level.